DOES CONTEXT AFFECT CODE SWITCHING? A CASE STUDY OF SAUDI ARABIC SELF-REPORTED CODE-SWITCHERS - Saeed Abdullah Alzahrani (Fonseca, Journal of Communication, 2025)
Code-switching is the use of two languages within a conversation. Bilinguals can adjust to social and cultural situations very easily. Socio-linguistic triggers have dominated previous research, but the personality and socio-biographical factors determining code-switching among Arab-English bilinguals in Saudi Arabia are generally less investigated. This is a quantitative study where the impact of age, education, language history, current language use, and personality dimensions of Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism, on code-switching behaviour was analysed. Self-reported questionnaires were used in gathering data from 74 participants that were analysed with SPSS. The sample had balanced gender distribution, and the average age was under 30. Pearson’s correlation analysis shows significant positive relations between cultural empathy and the frequency of code-switching (r = 0.37, p < 0.01), and also between emotional stability and code-switching with a stranger (r = 0.42, p < 0.001). Principal Component Analysis revealed that Openness and Extraversion were the most salient predictors of code-switching patterns. Contextual factors, including location (home, workplace) and the type of interlocutor (family, friends, colleagues), were found to significantly affect code-switching behaviour. Such results contribute to an understanding of bilingual communication in the dynamic interaction between personality traits, socio-biographical factors, and situational contexts. The research highlights the changing cultural environment in Saudi Arabia and opens up lines of future inquiry, such as class, ethnicity, and how technology influences bilingual practices.